Metodologia parcial de analisis proyecto "desarrollo del gusano cachon en la yuca" - Amézquita de Quinones, M.C. (International Center for Tropical Agriculture, 1977)
Part of the methodology of the analysis applied to the project of the hornworm (Erinnyis ello) on cassava is presented. The project studies the hornworm life cycle and population dynamics and the economic impact on cassava production under 2 conditions (1) in cages with controlled ideal conditions for development and (2) under field conditions on 19 farms with biological control by the egg parasite Trichogramma sp. and predation by Polistes erythocephalus (on 10 farms only). The theoritical structure of the Markov and semi-Markov stochastis processes is given; the models used are based on the latter. (CIAT)